2021
DOI: 10.1177/1548512921991245
|View full text |Cite
|
Sign up to set email alerts
|

Training data augmentation for deep learning radio frequency systems

Abstract: Applications of machine learning are subject to three major components that contribute to the final performance metrics. Within the category of neural networks, and deep learning specifically, the first two are the architecture for the model being trained and the training approach used. This work focuses on the third component, the data used during training. The primary questions that arise are “what is in the data” and “what within the data matters?” looking into the radio frequency machine learning (RFML) fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…2 depicts the relationship between the three dataset types discussed herein, and acknowledges that no dataset will ever consist of all relevant data. A more descriptive comparison of quality and quantity for these three dataset types is discussed in [57].…”
Section: A Simulated Vs Captured Vs Augmented Datasetsmentioning
confidence: 99%
See 4 more Smart Citations
“…2 depicts the relationship between the three dataset types discussed herein, and acknowledges that no dataset will ever consist of all relevant data. A more descriptive comparison of quality and quantity for these three dataset types is discussed in [57].…”
Section: A Simulated Vs Captured Vs Augmented Datasetsmentioning
confidence: 99%
“…As a result, synthetically generated RFML datasets can be good analogs for captured RFML datasets, if carefully crafted and known models exist for the simplistic environment. However, a recent AMC analysis [57] showed that, without considering channel effects, models trained on simulated datasets are insufficient when applied to real captured data (i.e. during realworld deployment).…”
Section: A Simulated Vs Captured Vs Augmented Datasetsmentioning
confidence: 99%
See 3 more Smart Citations